Preventing occupational injuries in the informal construction industry: a study protocol for the development of a safety education intervention for bricklayers and carpenters in Osun State, Nigeria - Ojo, Temitope Olumuyiwa; Onayade, Adedeji Ayodeji; Naicker, Nisha (Frontiers in Public Health, 2024)
Background: Occupational injuries are a growing public health problem. Approximately 1000 workers die daily from occupational injuries globally. Artisans working in the informal sector of the construction industry in many low/middle income countries like Nigeria have a higher injury predisposition. This study will assess the determinants of occupational injuries and design a safety intervention for informal sector artisans in the Nigerian construction industry.Methods: A sequential mixed-methods design will be employed to study 840 bricklayers and carpenters (420 per artisan group) in Osun State, Nigeria. Quantitative data will be collected first while qualitative data will be collected thereafter. Thirdly, a modified Delphi-technique will be employed to co-design a safety education intervention.For the quantitative study, artisans will be recruited via multi-stage sampling and a semistructured questionnaire will be administered to obtain information on artisans' sociodemographics, work-patterns and occupational injuries. A multivariable regression model will be used to determine the association between injury occurrence and independent variables.Twelve to sixteen focus group discussion (FGD) sessions will be conducted for artisans to obtain group perspectives about injuries and preferred safety training topics. From the FGD and quantitative study findings, a list of items for the safety training module will be compiled for the modified-Delphi process. Thereafter, the content validation index (CVI) will be derived and items with CVI of ≥0.80 will be included in the final safety training module.This paper describes the process required to assess the determinants of occupational injuries among artisans in the informal sector of the construction industry in Nigeria and further proposes the design of a context-relevant safety training intervention. The information from this study will be essential in promoting safe working environments for construction artisans.